THE FUNCTION OF CREDIT IN THE GROWTH OF SMALL AND MEDIUM BUSINESSES - Karimjonov Doniyorbek Ibrohimjon O’g’li (PT. Antis International Publisher, 2025)
Objective: The article aims to examine the role of credit in the development of small and medium enterprises (SMEs) and its broader impact on economic development. It focuses on understanding the importance of banking credit in a market economy and comparing key concepts related to credit functions. Method: A comparative analysis is conducted between the concepts of